GAMBARAN MOTIVASI BEKERJA PERAWAT DALAM MASA PANDEMI CORONAVIRUS DISEASE (COVID-19) DI BALI - Ni Putu Emy Darma Yanti; Ida Ayu Made Vera Susiladewi; Hary Pradiksa (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2020)
A professional nurse must have an obligation to care for all kinds of patients in various conditions, various need, including the COVID-19 pandemic. Nurses' concerns about their work have its impact on themselves which is can reduce nurses' work motivation. This study aims to describe the work motivation for nurses during the COVID-19 pandemic in Bali. This type of research is quantitative with a descriptive survey design on 193 nurses in Bali through purposive sampling technique. The results of data analysis found that the majority of nurses' work motivation during the COVID-19 pandemic was in the good category, namely 52.8%. The majority of nurses answered that they agreed on every item of the statement given regarding the work motivation of nurses except for points oneand two. The statement on point one